DATA WAREHOUSE MODEL BASED ON KIMBALL METHODOLOGY TO SUPPORT DECISION MAKING IN ASSET MAINTENANCE - Vasthu Imaniar Ivanoti; Muhammad Royani; Samidi Samidi (Jurnal Teknik Informatika (Jutif), 2023)
ITSM e-Prime is an ICT service management application based on ITSM framework owned by Pusintek that includes service desk, incident management, problem management, change management, release management, and configuration management processes. Currently there is a problem in determining the number of devices that will be included in the device maintenance contract or determining the number of devices that need to be replaced in a given year. The objective of this research is to build an asset management data warehouse so that it can be utilized by the Data Analysis and Presentation Team to produce a dashboard that presents data on network infrastructure assets that need to be maintained or replaced for budget planning needs. This descriptive verification analysis research used nine out of ninety tables from the ITSM e-Prime application and applied dimensional modeling Kimball to build a data warehouse because this methodology offers high query performance and understandable by end-user. The resulting data warehouse were tables in the form of star-schema. The tests were carried out by qualitative methods, namely quality testing by users (user acceptance test and blackbox testing) and quantitative method, namely comparing the number of infrastructure devices included in the maintenance contract in 2022. The final result of this research is a data warehouse consisting of fact table F_infrastructure and dimension table D_Merk, D_Area, D_Kategori, D_EoS, D_Garansi, and D_StatusPemeliharaan with acceptance percentage of 95% based on the test results.